Inhibitory peptide analogs derived from a major uveitogenic epitope protect from antiretinal autoimmunity by inducing type 2 and regulatory T cells - Cortes, Lizette M. (The Society for Leukocyte Biology, 2008)
We identified inhibitory peptide analogs (IPAs), capable of immunomodulating experimental autoimmune uveitis (EAU), induced in B10.RIII mice by immunization with the retinal antigen interphotoreceptor-binding protein in CFA. Alanine-substituted peptides of the major pathogenic epitope, residues 161–180, were synthesized. They were tested for immunogenicity, cross-reactivity with the native 161–180 epitope, pathogenicity, and ability to prevent EAU when given in IFA before EAU challenge with native murine (m)161–180. Two peptides, 169A and 171A, were unable to elicit disease but cross-reacted with m161–180 by lymphocyte proliferation. Mice pretreated with either of the substituted peptides failed to develop EAU after challenge with the native epitope, m161–180, and had reduced cellular responses by lymphocyte proliferation and by delayed hypersensitivity. Their cytokine response profile to m161–180 showed reduced antigen-specific IFN-γ and IL-17, whereas IL-4, IL-5, IL-10, and IL-13 from IPA-protected mice were increased, and serum antibody titers to m161–180 revealed reduced IgG2a and elevated IgG1 isotypes, suggesting a Th2 shift in the response. Protection was transferable with lymphoid cells from protected donors to naïve recipients, who were subsequently immunized for EAU. Thus, IPA pretreatment prevents induction of EAU by skewing the response to a subsequent uveitogenic challenge with the native peptide to a nonpathogenic phenotype, as well as by eliciting transferable regulatory cells.